The American Government and “Total War” on COVID-19 - Christopher Griffin (Angles)
In the Economic Impact Payment letter to American citizens in Spring 2020, President Donald Trump wrote that “we wage total war on this invisible enemy.” Trump likely did not intend to explicitly link this to the rich theory about “total war” in military history, but this article examines the American rhetoric surrounding the war on COVID-19 to see whether it corresponds to definitions of total war in military strategic thought. The Clausewitzian origins of the idea of “absolute war” and limited war will also be examined to ascertain their relevance as a framework for understanding the American approach to the conflict with the virus. A total war strategy would have implied either mobilizing the entire population into the health sector or imposing a total national lockdown. This article examines both the strategy outlined by Donald Trump and the reality of what was undertaken by the Federal Government. The military was involved in the war effort against the virus in the U.S., but only in a logistical and financial sense. A national lockdown was never intended due to its potential adverse effects on the economy, and in any case, the Federal Government did not have the authority to impose health policy on individual states and local authorities. The result was a variety of local responses to the crisis with little federal coordination, much like what occurred with the Influenza Epidemic of 1918-19. Despite its military and hyperbolic rhetoric, the Trump Administration did not choose a total war strategy. Instead, it decided to adopt a limited holding strategy that accepted human losses while protecting the economy and waiting for a Government-sponsored vaccine to save the day.